Health Policy Strategy for Controlling Pneumonia Disease - Dina Rawan G.Rana Dina (Health and Technology Journal (HTechJ), 2025)
The increase in pneumonia cases directly impacts the burden of health services, marked by a surge in the number of visits to service facilities, an increase in hospitalization rates, and high pressure on medical personnel in health centers and hospitals. This study analyzes the policy strategy for controlling pneumonia in Central Kalimantan. This study uses qualitative research with a descriptive phenomenological approach that emphasizes the health policy strategy for controlling pneumonia in Central Kalimantan to gain a deep understanding of the stakeholders' implementation. Based on the study's results, although the National Action Plan for controlling pneumonia focuses on toddlers, in Central Kalimantan, most cases of pneumonia are found in the pre-elderly age group (45-59 years), indicating a mismatch between national policies and local conditions. Environmental factors, air pollution, and comorbid conditions, such as chronic obstructive pulmonary disease (COPD) and diabetes, may not have been sufficiently considered in the policy. In Central Kalimantan, poor air quality due to forest fires and extreme climate change worsens health, especially in the pre-elderly age group. Therefore, the pneumonia control strategy in this area needs to be adjusted to local epidemiological conditions, environmental and social risk factors, socio-economic conditions, adjustments to prevention and treatment strategies, and collaboration between sectors, including focusing on adult, pre-elderly, and elderly age groups, not just toddlers.